Analisis Putusan Pengadilan Militer Terhadap Penyalahgunaan Senjata oleh Prajurit TNI - Sianturi, Catherine Rosalina; Lidowati, Alvina Maretia; Amalia, Firda; Rahayu, Cantika Tresna; Adam, Chelsea Kairadinda; Triadi, Irwan (Media Hukum Indonesia (MHI), 2025)
The misuse of firearms by members of the Indonesian National Armed Forces (TNI) constitutes a serious violation that not only breaches military discipline but also poses a threat to civilian security and public trust. This study aims to analyze the legal considerations in military court decisions involving soldiers who have misused firearms, as well as to assess the effectiveness of verdict implementation, the forms of legal accountability imposed, and the impact of public pressure on judicial proceedings. Using a normative juridical approach and case studies of several military court rulings, the findings indicate inconsistencies in sentencing, the influence of the defendants’ relationships with superiors, and a lack of transparency and internal oversight. Moreover, public pressure plays a significant role in shaping judicial outcomes—both as a driver of justice and as a potential threat to judicial independence. Reform of the military justice system is needed through strengthened oversight mechanisms, improved disciplinary training, and safeguarding judicial independence in order to achieve substantive justice and uphold public confidence